The sacred scroll and the researcher’s body: an autoethnography of Reform Jewish ritual - Ben-Lulu, Elazar (Journal of contemporary religion, 2022)
This article examines the relationship between the researcher’s body and the Torah scroll (Sefer Torah) during participant observation of a Jewish holiday ritual in an Israeli Reform congregation. Using an autoethnographic approach, I show how the Reform Jewish ritual demonstrates that the body is a charged religious symbol and the bearer of family traditions and unconscious understandings of the social order. Through this encounter, I discovered how my position in fieldwork on religion is located at the intersection of my ethnographic discipline, my religious habitus, and my identity as a gay man. Reflexive analysis of my active and passive behavior during the observation offered an opportunity to gain a deeper understanding of the differences between myself and the congregation. Thus, I suggest that anthropologists, even when researching their culture, must be aware of the elements that make up their own identities.